Internacionalização de empresa prestadora de serviço logístico e análise do comércio bilateral: Brasil e Itália - Cappelari, Maria Cecília (My University, 2025)
This study analyzes the feasibility of the internationalization of a Brazilian logistics company through the establishment of a commercial representation in Italy. The central objective is to assess whether the expansion is sustainable and strategically aligned with the company's context. The research adopts a qualitative and exploratory methodological approach, based on bibliographic research, documentary analysis, content analysis, and a case study. This combination allows for an in-depth understanding of the phenomenon, considering both objective and subjective aspects involved in the internationalization process. The analysis includes mapping the main Brazilian ports with the highest volume of exports to Italy, as well as identifying opportunities for commercial engagement. Based on the secondary data collected, scenarios of the company's potential participation in the bilateral logistics flow were developed, enabling estimates of the number of containers that could be handled, as well as projections of monthly and annual revenue, profit margins, and expected financial returns. The results show that the operation presents economic viability in the optimistic scenario, achieving investment recovery (payback) in approximately seven months. Overall, the indicators suggest that entering the Italian market is feasible and may strengthen the company's international competitiveness, especially if supported by local partnerships and strategic initiatives. [resumo fornecido pelo autor]
Este trabalho analisa a viabilidade da internacionalização de uma empresa brasileira de logística por meio da abertura de uma representação comercial na Itália. O objetivo central é avaliar se a expansão é sustentável e estrategicamente adequada ao contexto da empresa. A pesquisa adota uma abordagem metodológica qualitativa de caráter exploratório, fundamentada em pesquisa bibliográfica, documental, análise de conteúdo e estudo de caso. Essa combinação permite compreender o fenômeno em profundidade, considerando aspectos objetivos e subjetivos envolvidos no processo de internacionalização. A análise contempla o mapeamento dos principais portos brasileiros com maior volume de exportações destinadas à Itália, bem como a identificação de oportunidades de atuação comercial. A partir dos dados secundários levantados, foram desenvolvidos cenários de potencial participação da empresa no fluxo logístico bilateral, permitindo estimar o volume de contêineres que poderia ser intermediado, assim como o faturamento mensal e anual, margem de lucro e retorno financeiro esperado. Os resultados demonstram que a operação apresenta viabilidade econômica no cenário otimista, alcançando o retorno do investimento (Payback) em aproximadamente sete meses. No conjunto, os indicadores sugerem que a entrada no mercado italiano é viável e pode reforçar a competitividade internacional da empresa, especialmente se apoiada por parcerias locais e estratégias. [resumo fornecido pelo autor]
Keywords: Internacionalização de empresa; Logística; Exportação